CONSEQUENCES ON THE EXISTENCE OF ORAL COMMUNICATION APPREHENSION AMONG THE ENGLISH DEPARTMENT STUDENTS IN PRESENTATION CLASS AT RIAU ISLAMIC UNIVERSITY - Vitri Angraini Hardi (Journal of English Language and Education, 2018)
Dealing with the importance of having oral communication ability in English in the worldwide today, the thought on the importance of being able to speak in English is a must to survive in the fieldwork. The ability to speak in English in term of foreign language brings the advantage by those who are able to speak. In the fieldwork today, people who have ability to speak in foreign language, English particularly has some opportunities to compete in the fieldwork. However, it is not easy to acquire English and to use it in oral communication. Some factor plays on it, cognitive such as the competence on using the language, the ability to acquire the English skill, and also psychological. Mostly, the factors cause people’s inability to communicate orally is not people’s competence on the language, but psychological. It rises as the consequences on the present of communication setting. Since communication involves some elements such as audience, medium and others, it raises the students’ mental experiences definitely, in term of communication, namely apprehension. The students who enroll presentation class at Riau Islamic University experiences mental block during the presentation class. Consequently, experiencing oral communication apprehension causes the students’ difficulties in communication.